Evolution of Pneumatic Tsunami Simulators–From Concept to Proven Experimental Technique - Chandler, Ian; Allsop, William; Robinson, David; Rossetto, Tiziana (Frontiers in Built Environment, 2021)
This paper describes the evolution through three generations of pneumatic Tsunami Simulators for physical model tests of realistic tsunami. The pneumatic method, originally developed for tidal modelling in the Fifties, has been modernised to generate extraordinarily long waves in a controlled manner, with accurate reproduction of recorded free-surface tsunami field data. The paper describes how the simulator designs were developed and how they performed in the laboratory. Example results are presented from selected research studies that have validated their performance and then used them to quantify tsunami effects. Having described each of the 1st, 2nd, and 3rd generation Tsunami Simulators, the paper discusses how to calibrate the wave generation control to model tsunami with model periods 20 to 240s duration (equivalent to 2 to 20 minutes duration in prototype at 1:50 scale), many of which are far too long to ‘fit into the test flume’. The evolution of a composite approach to wave calibration is described with examples from 2nd and 3rd generation devices, demonstrated by successful simulation of both the 2004 Boxing Day, and the 2011 Great Eastern Japan (Tohoku) Tsunami at 1:50 scale.